Nearshore wave analysis in the Brazilian Northeast based on observations and numerical models. Issue 1 (2nd January 2018) - Gomes, Gabriel; Silva, Alex Costa da
ABSTRACT: This present study was based on the analysis of observational data on the spectral distribution of waves, collected off the southern coast of the state of Pernambuco, in northeastern Brazil, using a directional wave buoy, which was moored continuously over a three-year period (October 2011–November 2014). A partitioning method was used to determine the distribution of the main directional energy components of the swell and the types of wind sea waves. The wave spectrum energy partitioning data were used to obtain a detailed wave climate analysis for the study region, in which the relationship of each system (wind seas and swell) was considered in a directional characterisation of the wave climate. This empirical wave climate was then compared with the wave climate reanalysis available in the SMC-Brasil software package, which is widely used to simulate wave-driven dynamic coastal processes off the Brazilian coast. The analysis found that most components of the wave energy descriptions were statistically similar between the two approaches, except for the southern swells, which were identified in the wave buoy data, but not by the reanalysis.